A novel peptide Phylloseptin‐PBu from Phyllomedusa burmeisteri possesses insulinotropic activity via potassium channel and GLP‐1 receptor signalling - Long, Qilin (J Cell Mol Med, 2018)
Insulin, as one of the most important hormones regulating energy metabolism, plays an essential role in maintaining glucose and lipid homeostasis in vivo. Failure or insufficiency of insulin secretion from pancreatic beta‐cells increases glucose and free fatty acid level in circulation and subsequently contributes to the emergence of hyperglycaemia and dyslipidaemia. Therefore, stimulating the insulin release benefits the treatment of type 2 diabetes and obesity significantly. Frog skin peptides have been extensively studied for their biological functions, among which, Phylloseptin peptides discovered in Phyllomedusinae frogs have been found to exert antimicrobial, antiproliferative and insulinotropic activities, while the mechanism associated with Phylloseptin‐induced insulin secretion remains elusive. In this study, we reported a novel peptide named Phylloseptin‐PBu, isolated and identified from Phyllomedusa burmeisteri, exhibited dose‐dependent insulinotropic property in rat pancreatic beta BRIN‐BD11 cells without altering cell membrane integrity. Further mechanism investigations revealed that Phylloseptin‐PBu‐induced insulin output is predominantly modulated by K(ATP)‐[K(+)] channel depolarization triggered extracellular calcium influx and GLP‐1 receptor initiated PKA signalling activation. Overall, our study highlighted that this novel Phylloseptin‐PBu peptide has clear potential to be developed as a potent antidiabetic agent with established function‐traced mechanism and low risk of cytotoxicity.